The Heterogeneous Surface of Asteroid (16) Psyche. Issue 6 (15th June 2022) - Cambioni, Saverio; de Kleer, Katherine; Shepard, Michael
Abstract: Main‐belt asteroid (16) Psyche is the largest M‐type asteroid, a class of object classically thought to be the metal cores of differentiated planetesimals and the parent bodies of the iron meteorites. de Kleer, Cambioni, and Shepard (2021, https://doi.org/10.3847/psj/ac01ec ) presented new data from the Atacama Large Millimeter Array (ALMA), from which they derived a global best‐fit thermal inertia and dielectric constant for Psyche, proxies for regolith particle size, porosity, and/or metal content, and observed thermal anomalies that could not be explained by surface albedo variations only. Motivated by this, here we fit a model to the same ALMA data set that allows dielectric constant and thermal inertia to vary across the surface. We find that Psyche has a heterogeneous surface in both dielectric constant and thermal inertia but, intriguingly, we do not observe a direct correlation between these two properties over the surface. We explain the heterogeneity in dielectric constant as being due to variations in the relative abundance of metal and silicates. Furthermore, we observe that the lowlands of a large depression in Psyche's shape have distinctly lower thermal inertia than the surrounding highlands. We propose that the latter could be explained by a thin mantle of fine regolith, fractured bedrock, and/or implanted silicate‐rich materials covering an otherwise metal‐rich surface. All these scenarios are indicative of a collisionally evolved world. Plain Language Summary: Asteroid (16) Psyche is the target of the eponymous NASA mission, which will assess whether the asteroid is the exposed core of an early pre‐planet. The Atacama Large (Sub‐)Millimeter Array located on the Chajnantor Plateau in Chile allowed the acquisition of temperature images of Psyche at a resolution of 30 km/pixel (the highest ever achieved from Earth). We analyze these images to map the metal content of the first millimeters of the surface as function of longitude and latitude. We find that the relative abundance of metals and silicates varies across the surface. Additionally, we observe that the lowlands of a large depression change temperature much faster than the surrounding highlands as Psyche rotates on its spin axis. Based on this, we propose that the lowlands could exhibit ponds of fine‐grained materials, be highly fractured, and/or host silicate‐rich materials implanted by impacts. All these scenarios are indicative of an evolved surface processed by impacts. Key Points: Longitude‐latitude maps of the thermal inertia and dielectric constant of asteroid (16) Psyche derived from Atacama Large Millimiter Array data The surface of Psyche is heterogeneous and shows signatures suggestive of both metal‐ and silicate‐rich materials A depression on Psyche with distinctive thermal‐inertia properties suggests an evolved surface processed by impacts